Facile synthesis of substrate supported ultrathin two-dimensional cobalt-based metal organic frameworks nanoflakes. (July 2020) - Fu, Yu; Zhou, Hanmo; Yin, Sha; Zhou, Limin
Highlights: Ultrathin Co-MOF nanoflakes are homogeneously grown on hydrophilic carbon fibers. The length and density of Co-MOF nanoflakes can be controlled by growth time. Reactant concentration affects the morphology of Co-MOF nanoflakes. The Co-MOF nanoflake demonstrates its mechanical strength. Co-MOF nanoflakes can form a strong interphase with polymer, such as epoxy. Abstract: The synthesis of substrate-supported metal–organic-framework (MOF) nanoflakes has become a research hotspot due to its attractive use as precursors to prepare metal (oxide)/carbon nanocomposites for the applications of catalysis and energy storage. This work reports facile synthesis of a newly-structured ultrathin Cobalt-based MOF (Co-MOF) nanoflakes on carbon cloth (CC). Through changing reaction time and reactant concentration, Co-MOF morphologies can be easily controlled, which paves ways for controllable fabrication of ultrathin Co3 O4 nanoflakes on CC based on the phase transformation from Co-MOF to Co3 O4 . Meanwhile, the good compatibility of this mechanically strong Co-MOF with polymer inspires us to tailor CC@Co3 O4 from the perspective of polymer-based researches, such as polymer-based catalysts and solid state batteries using a solid state polymer electrolyte. Therefore, this study not only enriches the family of MOFs but lays foundations for fabrication of next-generation CC-reinforced polymer composites for multifunctional applications such as catalysis and energy storage.